Stakeholders' Perspective on Water Education Among School Students: A Case Study Of - Srikanthan, S.; Jeevasuthan, S. (Sri Lanka Institute of Information Technology, 2021)
Education is an important way to socialize the individual through change in his thoughts and attitudes. Water and related issues have emerged as major social problems in recent times. One section of the world suffers from dehydration while the other wastes water. This will lead to huge deficits of water in the future and will be a root factor for countless social problems such as disease, poverty, abuse and plunder. In this context, education on water and water security must be provided to all. The best way to do this is to introduce water education in the school curriculum as a compulsory subject and to incorporate it in extracurricular activities from primary to secondary education. The objective of this study is to discuss the importance of water education and how to develop it in the school curriculum. This research has adapted the qualitative method. The data for this study was collected primarily. through case studies and also by using the world café discussion method with stakeholders from selected educational sectors. This study emphasizes that the inclusion of education about water in our school curriculum is crucial to building a sustainable future community. This is because a living being cannot live in a world without water. The sole fact that water education will be included in the school curriculum of Sri Lanka it is not enough to improve the regional water security of the country because the awareness among the public about the importance of water and the changes that take place in relation to it is very low. Therefore, this study recommends the necessity to make water education an optional or compulsory subject in the Sri Lankan school curriculum for grades 6 to 9.
Keywords: School curriculum; Stakeholders; Water Education